Photocatalytic decomposition of gaseous formaldehyde using TiO2, SiO2−TiO2 and Pt−TiO2 - Byung-Yong Lee (International Journal of Photoenergy, 2003)
In this study, in order to improve the photocatalytic decomposition activities of formaldehyde, TiO2 catalyst modified with SiO2 substitution and metal (Pt, Cu and Fe) impregnation, were tested. In case of TiO2 substituted by SiO2, the optimal catalytic activity was found at the mole ration of 2 : 8. Among the metal impregnated TiO2, the Pt impregnated TiO2 showed the best activity even better than that of P-25 which is widely used in commercial application. However, Cu and Fe impregnated TiO2 showed the reverse effect. In the case of SiO2 substituted TiO2 the observed values of photoluminescence spectroscopy were quite proportional to the photocatalytic activities depending upon the mole ratio of SiO2 to TiO2. However, for the samples of metal impregnated TiO2, the reverse relationships were found. In UV-visible spectra for metal impregated TiO2, the transmittance value was reduced depending upon the loading of metals. The enhanced photocatalytic activity for high metal loading on TiO2 might be associated with the high concentration of excited electron that was monitored through UV-visible spectra.